Bootstrapping and Portability in Simulation Design - Kollars, Nina; Rosen, Amanda (International studies perspectives, 2016)
Despite the existence of a large literature on the use and effectiveness of simulations as part of the active learning pedagogical toolbox, simulations have yet to achieve wide adoption rates among college instructors. One of the principal constraints is time: traditionally, most simulations require extensive time for the faculty to design, prepare, and use in the classroom setting. This article examines two design features of simulations aimed at solving this problem—portability, where simulations are designed as a framework that can be used for different subjects, classes, and disciplines; and bootstrapping, or the tying of the simulation content to commonly known fictional or pop-culture scenarios. Combined, these two features can reduce some of the barriers to simulation use in the classroom. We conclude by illustrating both principles with a sample simulation called "The Trial of Goldilocks."